2022
DOI: 10.3389/fmicb.2022.829218
|View full text |Cite
|
Sign up to set email alerts
|

The N1038S Substitution and 1153EQTRPKKSV1162 Deletion of the S2 Subunit of QX-Type Avian Infectious Bronchitis Virus Can Synergistically Enhance Viral Proliferation

Abstract: The S2 subunit of infectious bronchitis virus (IBV) plays a critical role in the process of IBV infection. A comparison between the S2 subunit sequence of chicken embryo kidney cell (CEK) adapted virulent QX-like IBV strain SczyC30 (hereafter referred to as zy30) and its CEK-attenuated strain, SczyC100, revealed an N1038S substitution in S2 subunit and a 1154EQTRPKKSV1162 residue deletion in the C-terminus of the S2 subunit. In order to explore whether these two mutations are related to changes in the biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This finding could account for the discrepancy in the production of syncytia between zy100 and zy30. Our research discovered that the N1038S substitution is positioned in the HR2 region, with the 1154 EQYRPKKSV 1162 deletion in the cytoplasmic tail being essential for the function of the S2 subunit [ 8 , 49 ]. Alterations in these locations have a direct effect on S2 functioning, which causes Abl2 to become activated and strengthens the binding of actin, as well as causing the ENAH pathway to be indirectly activated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding could account for the discrepancy in the production of syncytia between zy100 and zy30. Our research discovered that the N1038S substitution is positioned in the HR2 region, with the 1154 EQYRPKKSV 1162 deletion in the cytoplasmic tail being essential for the function of the S2 subunit [ 8 , 49 ]. Alterations in these locations have a direct effect on S2 functioning, which causes Abl2 to become activated and strengthens the binding of actin, as well as causing the ENAH pathway to be indirectly activated.…”
Section: Discussionmentioning
confidence: 99%
“…Successive passages of Sczy3 with CEKs 100 times led to the creation of zy100, which is a variant of zy30 with a distinct S2 subunit that could generate bigger and greater numbers of syncytia when infected with CEKs. Thus, we conducted N1038S substitution and 1154 EQYRPKKSV 1162 deletion on rSczy3 to produce rSczy3S2-N1038S-CT9 ∆ (TCID 50 /mL = 10 7.23 ) [ 8 ]. The graphical representation of the contrast between CN, zy100, and zy30 with regard to amino acid composition, as well as the marked mutation sites, can be seen in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the real-time RT-qPCR assays, specific primer pairs were designed to amplify the viral RNA of IBV, the mRNA of the inflammatory factors IL-6, IL-8, IL-1β, and NF-κB, the mRNA of the innate immune related genes MDA5, TLR3, STING, Myd88, IRF7, and IFN-β, as well as β-actin, using Primer Premier 5.0 software (Premier Biosoft International) ( Table 1 ). The procedure for the quantification of viral load was performed as described previously ( Li et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The S2 subunit is a highly conserved part formed primarily by the heptad repeat regions, HRP1 and HRP2, and a fusion peptide that is responsible mainly for the viral entry and membrane fusion [48]. Research has shown that the S2 subunit is responsible for viral adaptation to various cell lines [52][53][54][55][56][57][58]. The S2 subunit also contains some minor neutralizing epitopes and contributes to the avidity and specificity of virus attachment, and thus viral host range [51].…”
Section: Infectious Bronchitis Virusmentioning
confidence: 99%